2020
DOI: 10.1007/s13592-020-00771-4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic stress resistance of bumblebee males: test case of Belgian species

Abstract: Thermotolerance has often been linked to species distribution for a diverse range of organisms. In the context of climate change, assessing heat resistance ability is useful for understanding potential future range shifts and the physiological response of populations. As bumblebee (Bombus ) populations have been declining for several decades with several documented range shifts, an assessment of the hyperthermic resistance of species is urgently needed. In this study, we measure in males the heat resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…Our results suggest that climate warming may favour aspects of bumblebee flight performance, such as motivation and endurance, across large parts of their geographical range. However, sensitivity to climate change can vary widely both between bumblebee species and across insect groups more generally (Arribas et al, 2012;Hamblin et al, 2017;Sunday et al, 2014;Zambra et al, 2020), and our results suggest that even within the same species, responses to temperature vary with body mass and thus likely affect smallerand larger-bodied taxa differently. It is therefore important that we quantify and compare flight and other key behavioural thermal response curves for species across the insect phylogeny to understand spatiotemporal risks and identify conservation priorities of similar and different functional groups.…”
Section: Con Clus Ionsmentioning
confidence: 72%
“…Our results suggest that climate warming may favour aspects of bumblebee flight performance, such as motivation and endurance, across large parts of their geographical range. However, sensitivity to climate change can vary widely both between bumblebee species and across insect groups more generally (Arribas et al, 2012;Hamblin et al, 2017;Sunday et al, 2014;Zambra et al, 2020), and our results suggest that even within the same species, responses to temperature vary with body mass and thus likely affect smallerand larger-bodied taxa differently. It is therefore important that we quantify and compare flight and other key behavioural thermal response curves for species across the insect phylogeny to understand spatiotemporal risks and identify conservation priorities of similar and different functional groups.…”
Section: Con Clus Ionsmentioning
confidence: 72%
“…Although B. t. terrestris queens were bigger, critical thermal limits did not differ among the subspecies. No significant correlation with body size was also found in studying heat resistance in males of 10 bumble bee species (Zambra et al, 2020). Furthermore, other selective pressures influence body size in bumble bees, as has been discussed in Gérard et al (2020), who found that queens of four bumble bee species became bigger over the last 100 year.…”
Section: Impact Of Body Size and Mass On Thermal Tolerancementioning
confidence: 95%
“…Recent evidence on thermal tolerances in terrestrial ectotherms accumulates in favor of a variant of this climate variability hypothesis, the climate extremes hypothesis, which predicts that selection for thermal tolerances strongly depends on rare but extreme thermal events (see Sundays et al, 2019 and refs therein). Although the pattern of higher heat resistance in males of widespread bumble bee species compared to those of more restricted, declining, or alpine species (Martinet et al, 2015;Zambra et al, 2020) might fit to this rule, more research is necessary to confirm and reveal to which extent periods of such extreme weather conditions impacts thermal tolerance breadths of B. terrestris or bumble bees in general.…”
Section: Thermal Tolerance Breadth In B Terrestrismentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of heat resistance in different bumblebee species is also presented (Martinet et al 2015;Oyen et al 2016;Zambra et al 2020). The heat resistance threshold temperature of high-elevation species (Bombus sylvicola and B. bifarius ) is nearly 5 °C lower than for lowelevation species (B. huntii ) (Oyen et al 2016).…”
Section: The Effect Of Species and Body Size On Bee Tolerance To Heatmentioning
confidence: 98%